Pengaruh Pemberian Ekstrak Umbi Bawang Putih (Allium sativum L.) dan Pupuk Kascing Cair terhadap Serangan Hama pada Tanaman Kailan (Brassica oleracea var. Alboglabra) - Saputra, Kelvin Indra; Adnyana, I Made Mega; Widaningsih, Dwi (Agrotrop : Journal on Agriculture Science; Vol 14 No 2 (2024), 2024)
The Influence of Garlic ( Allium sativum L.) Extract and Liquid Vermicompost Fertilizer to the Attack of Insect on Kailan ( Brassica oleracea var. Alboglabra ) Plantation. Kailan plant ( Brassica oleracea var. Alboglabra ) known as Chinese broccoli is one of the vegetable cabbage (Brassicaceae) family. One of the factors is that reduce quantity and quality of kailan plants are a high of pest attacks. The aim of study is to determine the effect of garlic extract and liquid vermicompost fertilizer on the type and abundance of pest populations, index of diversity, intensity of damage and determine the most effective concentration of garlic ( Allium sativum L.) and liquid vermicompost fertilizer. The research design as Randomized Block Design, with two treatment factors: garlic extract and liquid vermicompost fertilizer and level of concentration. Garlic extract was used as treatments, i.e 0g/l; 150g/l; and 300g/l. Liquid vermicompost fertilizer was used as treatments, i.e 0ml/plant; 10ml/plant; 20ml/plant; and 40ml/plant. Each treatment combination consists of 3 repetition so that there are 36 treatment of combination. The results showed that the dominant pests present in kailan plants are Atractomorpha crenulata and Plutella xylostella . The index of diversity in each treatment has a value of H<1 (Low). The treatments showed that as a single treatment has a significant effect. The treatments of 300g/l garlic extract and 40 ml/plant liquid vermicompodt fertilizer was the best concentration which gave on reduce the number of pest populations and intensity of damage also increased plant height and plant fresh weight, but there is no significant effect of interaction between both treatments.